Towards a natural classification of Pteridaceae: inferring the relationships of enigmatic pteridoid fern species occurring in the Sino-Himalaya and Afro-Madagascar - Schneider, Harald; He, Lijuan; Hennequin, Sabine; Zhang, Xian-Chun (Phytotaxa, 2013)
Using DNA sequences of the choroplast genome, we addressed the phylogenetic relationships of two understudied fern species belonging to the pteridoid clade of Pteridaceae. The two studied species occur in Afro-Madagascar and the Sino- Himalaya respectively. Our results recovered a sister relationship of the Sino-Himalayan Cerosora microphylla and the Afromadagascan Pityrogramma argentea. The latter is not closely related to the predominantly Neotropical genus Pityrogramma and is transferred to the genus Cerosora. Our results also confirmed the sister relationship of the predominantly Afromadagascan genus Actiniopteris and the predominantly Sino-Himalayan genus Onychium. These results contribute to the rapidly increasing body of evidence supporting the hypothesis of a frequent exchange between the Asian and Afromadagascan fern-floras during the Cenozoic and the formation of relict distribution ranges caused by Cenozoic climatic fluctuations and adaptation to local environments.